Implementation of Temperature and Humidity Control Devices in IOT-Based Hydrophonic Peppermint Cultivation at Sufiagrifarm Slawi - Maulana, Donny; Afriantoro, Irfan (Universitas Dian Nuswantoro and IndoCEISS, 2023)
Along with the rapid development of existing technology, especially in the field of information and the Internet of Thinks ( IoT ), which is developing so fast and producing a lot of benefits to help humans both in the field of education and in manufacturing and agriculture. But at this time there are still so many technologies that still cannot be implemented in certain fields, for example like agriculture, where everything is still done manually so that it takes a lot of time, costs and also more energy in the process. Such as the constraints that exist with Sufiagrifarm, where in this case to meet the needs of temperature and humidity in Peppermint plants that use a hydrophonic planting system it is still done manually by spraying the plants with a spray that produces dew. Given these problems, this research aims to assist Sufiagrifarm in overcoming problems in regulating temperature and humidity in peppermint plants so that temperature and humidity compliance in peppermint plants can be carried out automatically and can be monitored in real time. Development in this method is carried out using the SDLC Waterfall method. This application was created using the Java programming language using the MITApp inventor platform, for the tool itself it was made using an Arduino microcontroller with the C programming language supported by several other devices such as Thingspeak. The results of this study are to help fulfill temperature and humidity in peppermint cultivation at Sufiagrifarm.